ANALISIS BIAYA OPERASIONAL ALAT BERAT PADA PEKERJAAN TIMBUNAN PROYEK PEMBANGUNAN HOTEL 57 NGANJUK - Anugerah Islam Pribadi Santoso; Hanie Teki Tjendani (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
The development of the world of construction in this era has resulted in the increasing use and need for heavy equipment in every construction job. In the field of civil engineering, heavy equipment is used to assist humans in carrying out the work of constructing building structures. Even heavy equipment currently seems to be a vital resource in construction projects (Febrianti, 2018). The purpose of using this heavy equipment is to make it easier for humans to do their work so that the expected results can be achieved more easily in a relatively short time. In the construction of the Guets House 57 Nganjuk hotel, it certainly requires heavy equipment to make work easier, the heavy equipment used for heaps and excavations, namely Excavators and Dump Trucks, so that you can find out the time needed and the costs incurred for these 2 types of heavy equipment, the authors discuss in chapter 4 with a description of the volume of excavation work, namely 1,996 m3 and for the volume of embankment work, namely 1,387.28 m3 using 2 types of heavy equipment Exavator and Dump Truck with Mini PC 75 type for Exavator and Hino index 8 for Dump Truck from the calculation results of two types of heavy equipment it is obtained that the time for piling work is 9 days for Excavators and 6 days for Dump Trucks, for excavation work it takes 17 days for Excavators and 11 days for Dump Trucks, and for a daily fee of Rp. 3,675,816 for Excavators and Rp. 5,041,416 for Dump Trucks